2013
DOI: 10.1088/1674-1056/22/9/098803
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of a triple-junction thin-film solar cell based on μc-Si1−xGex:H

Abstract: In this paper, a-Si:H/a-SiGe:H/μc-SiGe:H triple-junction solar cell structure is proposed. By the analyses of microelectronic and photonic structures (AMPS-1D) and our TRJ-F/TRJ-M/TRJ-B tunneling-recombination junction (TRJ) model, the most preferably combined bandgap for this structure is found to be 1.85 eV/1.50 eV/1.0 eV. Using more realistic material properties, optimized thickness combination is investigated. Along this direction, a-Si:H/a-SiGe:H/μc-SiGe:H triple cell with an initial efficiency of 12.09% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…[9] The temperature coefficients of the bandgaps of a-Si, µc-Si, and β -FeSi 2 are 4.7×10 −4 eV/K, [24] 4.2×10 −4 eV/K, [25] and 3.1×10 −4 eV/K, [26] respectively. The Yunaz model [27,28] of the tunnel-recombination junction for simulating the triplejunction solar cell is employed. The simulated illumination is AM 1.5G, 100 mW/cm 2 .…”
Section: Methodologiesmentioning
confidence: 99%
“…[9] The temperature coefficients of the bandgaps of a-Si, µc-Si, and β -FeSi 2 are 4.7×10 −4 eV/K, [24] 4.2×10 −4 eV/K, [25] and 3.1×10 −4 eV/K, [26] respectively. The Yunaz model [27,28] of the tunnel-recombination junction for simulating the triplejunction solar cell is employed. The simulated illumination is AM 1.5G, 100 mW/cm 2 .…”
Section: Methodologiesmentioning
confidence: 99%
“…Nowadays, the triple junction silicon based thin film solar cell shows the state of art of conversion efficiency of 16.1% for p-i-n type [6] and 16.3% for n-i-p type [7]. The theoretical analysis of triple junction silicon thin film solar cell suggested that an optimum band gap of the bottom sub-cell absorber should be 0.9 [8] or 1.0 eV [9] depending on the type of the top and middle sub-cells. However, the band gap of the hydrogenated microcrystalline silicon (µc-Si:H) that generally has been used as the bottom sub-cell absorber was 1.1 eV which is not the optimal value.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Many thin film Si solar cells have been demonstrated, including singlejunction hydrogenated amorphous silicon (a-Si), [4] tandemjunction amorphous/microcrystalline silicon, [8] and triplejunction amorphous silicon. [9,10] However, the thickness of the absorber layer for thin film silicon solar cells is only about hundreds or thousands of nanometers, which is not sufficient to absorb long wavelength light for solar spectrum. [11] Therefore, the power conversion efficiency (PCE) of thin film Si solar cells is relatively low compared with those of crystalline silicon and polycrystalline Si solar cells.…”
Section: Introductionmentioning
confidence: 99%